Usability and User Experience Evaluation of Touchable Holographic Solutions: A Systematic Mapping Study - Campos, Thiago Prado De; Damasceno, Eduardo Filgueiras; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Interacting with holograms using the hands is on track to reach a broad audience in the coming years. Therefore, a current challenge is understanding how to evaluate this new interaction scenario concerning Usability and User eXperience (UX). In this use context, the user interacts with virtual objects in your real environment. Some already known evaluation technologies have been applied to this type of solution, although they were not created considering aspects such as immersion and presence, typical in this interactive environment. Thus, this paper presents a Systematic Mapping Study (SMS) that sought to identify usability and UX evaluation technologies applied to touchable holographic solutions in augmented reality or mixed reality environments. Furthermore, the SMS sought to answer questions about evaluation technologies and holographic solutions. The SMS examined 3551 publications and selected 40 that presented 106 usability or UX evaluation technologies in a touchable holographic solution. The results shed light on methods and aspects little addressed and showed patterns and preferences for combinations of devices, gestures, and feedback types. This work contributes to HCI researchers by better understanding the state of the art of usability and UX evaluation technologies applied to touchable holographic solutions, classifying them, and discussing the main gaps and opportunities.